Statistical Channel Impulse Response Modeling for Optical Wireless Communication in Turbid Waters - Boluda-Ruiz, Rubén; Rico-Pinazo, Pedro; Castillo-Vázquez, Beatriz; García-Zambrana, Antonio; Qaraqe, Khalid (URSI'19 (Sevilla, septiembre, 2019), 2019)
Underwater optical wireless communication (UOWC) systems support high-speed, reliable and cost-effective implementations that are demanded for extending the telecommunication networks to oceans. UOWC systems suffer from attenuation and scattering processes. Particularly, the scattering process can change the direction of the emitted photons, especially in turbid waters. In this way, quantifying the signal attenuation and the time dispersion produced by absorption and scattering is a crucial work. Hence, we propose a new closed-form solution for modeling the channel impulse response for UOWC systems in turbid water that is validated through Monte Carlo simulations and can be used for system design and optimization purposes.
Keywords: Comunicación; Telecomuncaciones; Underwater optical wireless communications; Turbid waters; Attenuation and scattering processes